(untitled) (Modern education and development, 2025)
This article examines the pragmatic dimensions of teacher speech in educational settings and their impact on the teaching-learning process. Drawing on pragmatic linguistics, discourse analysis, and educational research, the study explores how teachers’ linguistic choices, speech acts, and communicative strategies influence classroom dynamics, student comprehension, and knowledge construction. The analysis focuses on key pragmatic features including speech acts, implicature, politeness strategies, and contextual adaptation in classroom discourse. Findings suggest that effective teaching is intrinsically linked to teachers’ pragmatic competence—their ability to adapt language use to specific educational contexts, learning objectives, and student needs. The article highlights how conscious attention to the pragmatic dimensions of classroom discourse can enhance pedagogical effectiveness, foster more inclusive learning environments, and facilitate deeper student engagement. Theoretical implications for teacher education programs and practical applications for classroom practice are discussed, emphasizing the need for explicit development of pragmatic awareness among teaching professionals.